STRATEGI PENGEMBANGAN WISATA PEMANCINGAN KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Alam, Syamsul (Katalogis, 2016)
The research aims to find out, to analyze and to formulate the right strategy in developing fishing tourism in Sigi District of Sigi Regency. Population of the research was 4 entrepreneurs of fishing tourism spot in Sigi District. This was a descriptive research with qualitative approach. The data were collected through questionnaire, interview, observation and documentation. The data were analyzed using SWOT analysis. The results indicated that: (1) strengths and weakness have the highest score compared to opportunities and threats in fishing tourism development strategy of Sigi District, Sigi Biromaru Regency, so that it should put combination strategy between strength-opportunities for the position of fishing entrepreneurs in internal and external matrixes from now on and for future in developing the fishing tourism object; (2) the recommended strategy to develop the fishing tourism is strength-opportunities strategy, which means the strategy using strength to utilize with action plan as alternative as follow: (i) utilizing natural resources as high demand of business/fishing place; (ii) increase a good partnership and relationship among fishing entrepreneurs with low competition climate; (iii) make local development priority as the local income source; (iv) utilizing the easiness of gaining material and availability of facilities in developing fishing pool; (v) workers number should be sufficient with the growth of fishing business; and (vi) increasing motivation in the effort to fulfill facilities in fishing pool development.